Diagnostic investigations of DKK‐1 and PDCD5 expression levels as independent prognostic markers of human chondrosarcoma. Issue 7 (3rd June 2016) - Zarea, Mojtaba; Mohammadian Bajgiran, Amirhossein; Sedaghati, Farnoush; Hatami, Negin; Taheriazam, Afshin; Yahaghi, Emad; Shakeri, Mohammadreza
Abstract: In this study, we investigated the expression levels of Dickkopf‐1 (DKK‐1) and programmed cell death 5 (PDCD5) by using quantitative real‐time PCR and immunohistochemistry in patients with chondrosarcoma. The DKK‐1 mRNA levels were significantly higher in chondrosarcoma when compared with the corresponding nontumor tissues (mean ± SD: 4.23 ± 1.54; 1.54 ± 0.87; P  = 0.001). PDCD5 mRNA levels were remarkably deceased in tumor tissues when compared with corresponding nontumor tissues (mean ± SD: 1.94 ± 0.73; 5.42 ± 1.73; P  = 0.001). The high and moderate DKK‐1 expressions were observed for 60% of chondrosarcoma samples in comparison with 27.5% of corresponding nontumor tissues ( P  =  0.001). Moreover, low expression of PDCD5 was found in 67.5% of the tumor tissues when compared with the nontumor tissues (32.5%; P  = 0.002). The results of this study showed that high DKK‐1 expression levels were strongly related to MSTS stage ( P  = 0.011) and the advancement of histological grade ( P  < 0.001). Furthermore, the PDCD5 expression levels were correlated with histological grade ( P  < 0.001), MSTS stage ( P  = 0.016), and distant metastasis ( P  = 0.001). Kaplan‐Meier survival and log‐rank survival showed that patients with high DKK‐1 levels and low PDCD5 levels were correlated with shorter overall survival (log‐rank test P  < 0.001). PDCD5 levels, histological grade, and tumor stage were independent predictors of overall survival. In conclusion, DKK‐1 and PDCD5 can be independent predictors of overall survival in patients suffering from chondrosarcoma. © 2016 IUBMB Life, 68(7):597–601, 2016